Optimizing Microbial Enhanced Oil Recovery through Nutrient Optimization in Indonesia Field - Manihuruk, Jasmine Christiana; Kurnia, Rani (Journal of Earth Energy Science, Engineering, and Technology, 2025)
Microbial Enhanced Oil Recovery (MEOR), a tertiary recovery technique designed to extract residual oil retained in reservoir pores that are not accessible through conventional extraction methods. By harnessing the capabilities of microorganisms, MEOR improves oil recovery through the generation of bioproducts, including biosurfactants, solvents, gases, and biopolymers. This research focuses on the stimulation of indigenous microbes (microorganisms already existing within the reservoir) by injecting a formulated nutrient solution. The objective is to trigger the metabolic activity of these microbes to produce biosurfactant as metabolite. This research investigates the unique and rapid MEOR response in the TM-X well of Field X, Indonesia. The methodology involved spontaneous imbibition experiments using Berea core samples saturated with TM-X crude oil. A comparison was made between a control system using native brine and a treatment system using brine enriched with an optimized nutrient formula (molasses, NPK, and DAP). The findings revealed a remarkable acceleration in oil recovery for the TM-X well, with the recovery factor increasing from a baseline of 31% to 58% within the first 24 hours. This led to the determination of an exceptionally short optimal soaking period of just one day. This rapid response is attributed to the highly efficient microbial consortium in Field X, which demonstrated swift and potent biosurfactant production. This was evidenced by a reduction in interfacial tension (IFT) from 2.05 dyne/cm to 0.136 dyne/cm and, notably, a simultaneous decrease in oil viscosity from 27.91 cP to 20.76 cP. This study highlights the significant potential of a site-specific MEOR application in Field X, where rapid microbial action can lead to highly efficient and accelerated oil recovery. Overall, the research contributes valuable insights into optimizing MEOR methodologies, highlighting the importance of nutrient optimization in enhancing oil recovery.